Aplikasi Optimalisasi Penjadwalan Proyek dengan Metode Harmony Search (Studi Kasus: AKSDAI) - Yusida Widana (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
Scheduling is one of the important stages in the industrial world, especially in terms of building a building. Usually in handling a development project, resources are available in a limited amount of resources. The purpose of project scheduling is to optimize project scheduling with the Harmony Search method. Harmony Search method is a method that adopts the process of finding a blend of tones in order to obtain beautiful musical harmony. Similarly, the optimization process that looks for optimal or perfect solutions based on functions and objectives. Harmony Search (HS) was first introduced by Zong Woo Geem in 2001. The basic idea of ​​Harmony Search is to mimic the process of improving the harmony of music undertaken by music choir groups. When a music choir makes improvements to the harmony of the music being played, there will be three possible choices, including playing well-known harmony music based on their memories, playing harmony music that is similar to well-known harmony music but there is little adjustment, or making harmony music that is new.